PROCLAMA SOBRE EL AMBIENTE HACIA UN NUEVO ORDEN ECOLÓGICO DE COOPERACIÓN INTERNACIONAL - Calderón Fournier, Rafael Ángel (2015)
In recent decades, humans have experiencedrapid growth and therefore the increasein demand for natural resources on the planetthat is why people need to develop an ecologicalconscience to decide the fate of life on theplanet, as the depletion of natural resourcesand environmental degradation have a directimpact on achieving peace, democracy andrespect for human rights in a country.